Utilisation of noise suppression techniques in the development of two-stroke, stratified-charge, lean-burn gasoline engines - Abd. Rahman, Roslan; Kamsah, Nazri; Abd. Latif, Zulkarnain (Universiti Teknologi Malaysia, 2005)
New two-stroke gasoline engines were to be developed by Universiti Teknologi Malaysia. This project is intended to fulfill the noise and vibration requirements in the development of two-stroke engines. The objective is to adopt current state-of-art technologies in noise, weight and vibration reduction without compromising the criteria for high power-to-weight ratio, low emission, low fuel consumption and multiple platform applications. Overall vibration on existing engines was carried to identify the dominant frequency range and vibration level. Vibration simulation using FEM was done on the proposed new engine and some modifications were proposed. Noise radiation simulation was also carried out on the proposed and modified engine models to ensure uniform distribution of noise. Balancing calculations on three types of engines were analyzed as well. The effect of back-pressure in exhaust system, the usage of catalytic converter and new materials on engine components, the calculation of heat loss from engine surface were also included. Exhaust and intake for the new engine were designed to complete the system. Parameter analysis was also carried out for both intake and exhaust. The prototype engine was finally tested for noise radiation by using sound intensity technique to identify possible dominant noise radiation sources. It was concluded that the prototype engine produced acceptable amount of noise radiation at no load condition.